Multicenter study for the treatment of sidewall versus bifurcation intracranial aneurysms with use of Woven EndoBridge (WEB) - Adeeb, Nimer; Dibas, Mahmoud; Diestro, Jose Danilo Bengzon; Cuellar-Saenz, Hugo H.; Sweid, Ahmad; Kandregula, Sandeep; Lay, Sovann V.; Guenego, Adrien; Renieri, Leonardo; Sundararajan, Sri Hari; Saliou, Guillaume; Aslan, Assala; et al. (Radiology, 2022)
Background - The Woven EndoBridge (WEB) device was explicitly designed for wide-neck intracranial bifurcation aneurysms. Small-scale reports have evaluated the off-label use of WEB devices for the treatment of sidewall aneurysms, with promising outcomes. - Purpose - To compare the angiographic and clinical outcomes of the WEB device for the treatment of sidewall aneurysms compared with the treatment of bifurcation aneurysms. - Materials and Methods - A retrospective review of the WorldWideWEB Consortium, a synthesis of retrospective databases spanning from January 2011 to June 2021 at 22 academic institutions in North America, South America, and Europe, was performed to identify patients with intracranial aneurysms treated with the WEB device. Characteristics and outcomes were compared between bifurcation and sidewall aneurysms. Propensity score matching (PSM) was used to match by age, pretreatment ordinal modified Rankin Scale score, ruptured aneurysms, location of aneurysm, multiple aneurysms, prior treatment, neck, height, dome width, daughter sac, and incorporated branch. - Results - A total of 683 intracranial aneurysms were treated using the WEB device in 671 patients (median age, 61 years [IQR, 53-68 years]; male-to-female ratio, 1:2.5). Of those, 572 were bifurcation aneurysms and 111 were sidewall aneurysms. PSM was performed, resulting in 91 bifurcation and sidewall aneurysms pairs. No significant difference was observed in occlusion status at last follow-up, deployment success, or complication rates between the two groups. - Conclusion - No significantly different outcomes were observed following the off-label use of the Woven EndoBridge, or WEB, device for treatment of sidewall aneurysms compared with bifurcation aneurysms. The correct characterization of the sidewall aneurysm location, neck angle, and size is crucial for successful treatment and lower retreatment rate. - © RSNA, 2022 - See also the editorial by Hetts in this issue.
Gesehen am 06.03.2023